Industri Pertahanan Indonesia Dikaitkan Situasi Dan Kondisi Peperangan Asimetris - Akbar, Yudhi (Journal of Industrial Engineering & Management Research, 2022)
Abstract — Globalization has had a great impact in transforming every aspect of people's lives around the world as a result of the rapid development of information and telecommunications technology. In this change there is a phenomenon that allows excesses to potentially become a threat to the security of a country. The process of realizing national integration often faces obstacles and threats, especially in the field of defense and security as well as the Indonesian defense industry. The threat of non-state actors currently appears in various forms, among which non-conventional threats are called asymmetric wars. So that it has a significant impact on the industrial world, especially in the Indonesian defense industry. In the research discussed, qualitative methods are used with interviews, observations and literature study approaches. The theory used in this research is asymmetric warfare in the Indonesian defense industry. The result of this research is the development of the defense industry is closely related to the situation and conditions of asymmetric warfare, which can affect the level of technological sophistication owned by both the state. In Indonesia, the situation and condition of asymmetric warfare is a form of threat faced by threatening national defense in the perspective of Indonesian national defense and security, especially in the defense industry.